Care management in nursing within emergency care units - Tono de Oliveira, Roberta Juliane; Vieira Hermida, Patrícia Madalena; da Silva Copelli, Fernanda Hannah; Guedes dos Santos, José Luís; Lorenzini Erdmann, Alacoque; de Andrade, Selma Regina (Investigación y Educación en Enfermería, 2015)
Objective. Understand the conditions involved in the management of nursing care in emergency care units. Methodology. Qualitative research using the methodological framework of the Grounded Theory. Data collection occurred from September 2011 to June 2012 through semi-structured interviews with 20 participants of the two emergency care units in the city of Florianopolis, Brazil. Results. Hindering factors to care management are: lack of experience and knowledge of professionals in emergency services; inadequate number of professionals; work overload of emergency care units in the urgent care network; difficulty in implementing nursing care systematization, and need for team meetings. Facilitating factors are: teamwork; importance of professionals; and confidence of the nursing technicians in the presence of the nurse. Conclusion. Whereas the hindering factors in care management are related to the organizational aspects of the emergency care units in the urgency care network, the facilitating ones include specific aspects of teamwork. How to cite this article: Oliveira RJT, Hermida PMV, Copelli FHS, Santos JLG, Erdmann AL, Andrade SR. Care management in nursing within emergency care units. Invest Educ Enferm. 2015; 33(3):